Dampak Penerapan Fuel Surcharge pada Maskapai Wing Air Layanan No Frills terhadap Load Factor Rute Surabaya – Yogyakarta - Kinarya, Dani Eka; Kusuma, Nur Makkie Perdana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
There was an increase in world oil due to geopolitical conflicts, this increase in fuel prices had an impact on the aviation industry, namely an increase in the price of avtur or aircraft fuel. One of them is Wing Airlines with a propeller-engined aircraft, namely ATR-72, expressed a complaint in the conditions experienced to ask for an adjustment in the price of airplane tickets for assistance from the government due to the avtur cost component which eats up operational costs. This study aims to determine the impact factors of the increase in aircraft fuel prices in the application of a new component called Fuel Surcharge. In addition, this study also aims to find solutions to overcome the impact of rising fuel prices by Wing Airlines on the Surabaya - Yogyakarta route. This research is descriptive using qualitative methods with data collection methods in the form of interviews, observation, and documentation. The data obtained is in the form of interviews with Wing Air Airline officers at Juanda International Airport as well as documents used to carry out daily activities. The results of this study indicate that the factors that increase passenger ticket fares in fuel operational costs are due to rising world oil prices, so that government regulations are imposed, namely applying a fuel surcharge component of 25% of the base price rate charged to service passengers. air freight. In the results the data obtained does not show a drastic change in the number of passengers (Load Factor) so that the increase in ticket prices does not have an effect on the number of passengers (Load Factor) to adjust fuel operational costs but additional costs (Fuel Surcharge) have been determined and determined by the government to parties airline to apply to the specified route. Keywords: Avtur increase, Fuel Surcharge, Load Factor